An Exploratory Study of the Balance Quality of CSR Reports of Ten Chinese Organizations - Peng, Xinyi (Auckland University of Technology, 2018)
The aim of this study is to explore whether ten selected Chinese organizations disclosed a balance quality information in their corporate social responsibility (CSR) reports. Previous studies have been done to assess the quality of CSR disclosure in western countries, but research is still lacking on the reporting quality of Chinese organizations. This study fills the gap and contributes to the existing literature by assessing the one of the quality principles suggested by GRI, balance quality, of CSR reports in China. This study is motivated by Boiral’s study (2013) and decides to focus on the investigation of balance in Chinese CSR reports. The results show that most examined Chinese CSR reports did not exhibit good balance; 85% of significant negative events were not disclosed in the reports. Positive sentences accounted for more than half the overall content of most analyzed CSR reports. The result suggests that Chinese managers communicate CSR information in a biased way. This study introduces the Chinese concept of face to explain the unbalanced results observed. It also provides some useful recommendations for future research.
Keywords: CSR; Corporate Social Responsibility; China; Balance; GRI; Quality of CSR reports